Anatomy of skeleton axiale of squirrel - Atalar, O; Yilmaz, S (Indian Veterinary Journal, 2004)
The rodents, which are the largest order of placental mamma Is, comprise of more than half of the mammals known at present day. The subject of this study is squirrel. belonging to Sciuridae family, which constitutes a small group of order Rodentia. (Demirsoy, 1992; Karol, 1963; Kuru, 1987). Despite anatomical studies on the osteology of wild animals such as the wolf and the fox (Girgin et al., 1988), the fox and the jackal (Gultekin and Ucar, 1980), the badger (Dinc. 2001; Atalar and Cakir, 2003), the mink (Dursum and Tipirdamaz, 1989), the hyena (Tecirlioglu, 1983), wild sheep and goat (Tasbas, 1978, 1983), the porcupine from Rodentia (Yilmax, 1998) and the otter (Dinc et al., 1999; Yilmaz et al., 2000), the osteology of squirrels has not been studied in detail. So this study was aimed to investigate the axial skeleton of squirrels, thereby making a contribution to filling the gap of knowledge in this field.